Pembuatan Biodiesel Dari Limbah Minyak Ikan Patin Menggunakan Reaktor Membran - Silvia Rahmi; Syarfi Syarfi; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Membrane reactor is an alternative technology is used to produce of biodiesel, one of the advantages of the reaction and separation process takes place in a single stage simultaneous. This research aims to study the effect of the variation of the catalyst and mole ratio feed catfish oil - methanol in biodiesel production, transesterification process in a membrane reactor with a variation of the mole ratio of catfish oil - methanol 1:10, 1:14, and 1:18, the concentration of the base catalyst 0,5% -wt, 1% -wt and 1,5% -wt, pressure transmembrane 1 and 2 bar and a temperature of 60 oC process. The results showed biodiesel production using membrane reactor reached 93,89 % yield on the condition of the mole ratio of 1:14 with a concentration of 1,5 %-wt, characteristics of biodiesel produced meets the quality standards of biodiesel in Indonesia including biodiesel, density 857,3 kg/m3, kinematic viscosity of biodiesel is 5.6 mm2/s, Flash Point 145 °C, Acid Number 0.549 mg-KOH/g, Cetane Number 53,72.Keywords : biodiesel, catfish oil, transesterification